Act for international development ("Point IV" program). Hearings before the committee on foreign affairs. House of representatives. Eighty first Congress. First and second sessions on H.R. 5615, H.R. 6026, H.R. 6834, H.R. 6835, and H.R. 7346. Bills to promote the foreign policy of the United States and to authorize participation in a Cooperative endeavor for assisting in the development of economically underdeveloped areas of the world. Part 2. January 12, 13 and 17, 1950 (United States Government Printing Office, 1950)
With ills., index, map and tabs.